2022
DOI: 10.3389/fphys.2022.835705
|View full text |Cite
|
Sign up to set email alerts
|

Road to Tokyo 2020 Olympic Games: Training Characteristics of a World Class Male Triathlete

Abstract: There is a growing interest in the scientific literature for reporting top-class endurance athletes training programs. This case study reports on the training program of a world-class male triathlete preparing to compete in the Tokyo 2020 Olympic Games. A macrocycle of 43 weeks is presented. The triathlete performed 14.74 ± 3.01 h of weekly endurance training volume. Training intensity distribution (TID) was 81.93% ± 6.74%/7.16% ± 2.03%/10.91% ± 6.90% for zones 1 (low intensity, <VT1), 2 (moderate inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 59 publications
2
21
1
Order By: Relevance
“…The triathletes showed increases of ≈20% in VO 2max over the seasons. Both triathletes achieved a high VO 2max (<80 mL/kg/min) value as reported for other top endurance athletes such as a professional cyclist (87 mL/kg/min), a world‐class triathlete (84 mL/kg/min) or elite marathon runners (81.0 ± 4.0) 8,9,44 . Both triathletes achieved a relative power value at VO 2max and at ventilatory thresholds slightly above that of U23 cyclists but below that of professional cyclists 29 .…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The triathletes showed increases of ≈20% in VO 2max over the seasons. Both triathletes achieved a high VO 2max (<80 mL/kg/min) value as reported for other top endurance athletes such as a professional cyclist (87 mL/kg/min), a world‐class triathlete (84 mL/kg/min) or elite marathon runners (81.0 ± 4.0) 8,9,44 . Both triathletes achieved a relative power value at VO 2max and at ventilatory thresholds slightly above that of U23 cyclists but below that of professional cyclists 29 .…”
Section: Discussionsupporting
confidence: 64%
“…In the 2019 season example, the TID changed from an HVT and a pyramidal distribution in the first weeks of the season to a polarized distribution, which was used as the main model from week 12 onwards. This evolution from a pyramidal distribution to a polarized one has been observed to be positive in other studies 9,50 . Filipas et al 50 found that the evolution from pyramidal to polarized TID in a 16‐week training block allowed to maximize performance improvements and some physiological variables such as VO 2peak, and a velocity at 2 and 4 mmol/L of blood lactate concentration in a group of well‐trained runners.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this line, training groups are often seen, in which athletes with different objectives, moments of the season, age, or even competitive level are mixed; training in situations far from those that can be found in competition. In addition, in most competitions there is little knowledge of the competition that does not allow either coaches or athletes to predict the final result [ 12 ]. To do this, the tactic or approach of the competition is used.…”
Section: Introductionmentioning
confidence: 99%